(untitled) (Journal of Environmental Science and Natural Resources, 2016)
The study was conducted to assess the level of Cu, Zn, Pb, Cr, Fe, Mn, Cd and Ni contamination in the water samples of the Buriganga river. Total 14 water samples were collected from different areas of upstream of the Buriganga river to determine the physicochemical properties, concentration of different metallic constituents and assess the heavy metal pollution load. Atomic Absorption Spectrometer was used for analyzing the heavy metals of the samples. The mean concentration of Ca, Mg, Na, K in water samples were 0.779, 0.889, 140.39, 26.9 ?g mL-1, respectively. The mean concentration of Cr, Pb, Fe, Cu, Zn and Mn in the water samples were 0.17, 0.05, 0.67, 0.22, 0.55 and 0.17 ?g mL-1, respectively. The amount of Cd in all samples and Pb in 10 samples was below detectable limit of the instrument (0.01 ?g mL-1). Water pH ranged from 4.09 to 7.41 and EC was 346 to 7720 µS cm-1. Magnitude of heavy metal pollution in the Buriganga river system implies that the condition is very alarming and may severely affect the aquatic ecology of the river. To minimize the severe impact on city dwellers and aquatic ecology of the Buriganga river, sustainable steps and continuous monitoring on pollution prevention and cleanup operation is suggested. J. Environ. Sci. & Natural Resources, 8(2): 141-146 2015